Pemberdayaan Masyarakat Melalui Kegiatan KKN Uniflor Mengabdi di Desa Nduaria Kabupaten Ende - Liru, Marianus Woda; Celmi, Yuliana; Rendo, Margareta Dian Arimbi Puspa; Ndora, Yustanti Herlina; Anvianita, Yuliana; Babo, Bernadeta; Radja, Maxmiliano Cavalero; Neno, Maria Fatima; Sara, Emanuel Hendra; Dhone, Lidia L; Paut, Sophieni Bintang Princessha; Ndiu, Marnelia; Dala, Evenritus K; Muda, Stanislaus Novantus; Koda, Josua Jors Wake; Jeong, Susana Oktavia (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Nduaria Village, located in the Kelimutu sub-district of Ende Regency, East Nusa Tenggara Province, is predominantly an agricultural community. The primary goal of KKN program was to apply the knowledge gained during their university studies and address the needs of the local community. The KKN program also aimed to develop students' character, leadership, and social skills. Despite the short duration of the program, students were able to identify key issues in the village, such as water shortages, lack of environmental cleanliness, and low English language proficiency among students. The implementation involved various activities, including educational workshops and tree planting. The students held English language lessons for primary school students, as well as early childhood education programs for preschool and kindergarten children. In addition, they organized socialization on environmental cleanliness and anti-bullying awareness for the village schools. A significant environmental initiative was the planting of trees to help address the village's water scarcity. The KKN program also included communal cleaning activities, aimed at raising awareness about environmental hygiene. The program was well-received by the local community, with high participation from village officials, youths, and school children. Through the KKN, students were able to make a positive contribution to the village's development in the areas of education and environmental conservation, while also gaining valuable real-world experience. Overall, the program helped foster enthusiasm among the students and local community to work together for a better future. The Community Service Program (KKN) is a tangible manifestation of the responsibilities of lecturers and students in serving the community. The purpose of this service is to enhance students' awareness and empathy, instill values such as work ethic, perseverance, responsibility, leadership, independence, and entrepreneurship, as well as to contribute by solving problems in the community.